Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter R - Review of Basic Concepts - R.7 Radical Expressions - R.7 Exercises - Page 74: 10



Work Step by Step

RECALL: (1) $(a+b)(a-b) = a^2-b^2$ (2) For $a\gt0$, $(\sqrt{a})^2 = a$ Use rule (1) above by to obtain: $=2^2 - (\sqrt{3})^2 \\=4-(\sqrt3)^2$ Use rule (2) above to obtain: $\\=4-3 \\=\color{blue}{1}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.